The everything guide to informational texts, K-2 : best texts, best practices - Barclay, Kathy (Thousand Oaks, Calif. : Corwin, 2014)
Many educators, overwhelmed by the increasing demands of the profession and by the effort that the move to the Common Core Standards requires, continue to view fiction text as the primary source for both read aloud experiences and beginning reading instruction. This text helps all educators and prospective educators see nonfiction texts as an important component of all aspects of the PreK-2 curriculum and to provide them with practical, proven tools for selection and use of a wide variety of informational literature, including books, magazines, charts, graphs, digital media, and more. The authors examine why a balance of informational and narrative text is so important, and what recent research reveals about the value of using nonfiction text with young children. Those working most closely with children in kindergarten through second grade classrooms will find this to be a practical resource for understanding the Standards related to nonfiction text, and for selecting and using appropriate informational literature to build young children's background knowledge and their acquisition of foundational reading skills.
Contents note continued: Second Grade Informational Text Standards Included -- Other Standards Addressed -- ch. 9 Embedding Informational Texts in Units of Study -- An Interdisciplinary Focus -- Planning Units of Study: Who Does What? -- Selecting High-Quality Informational Literature for Units of Study -- Characteristics of Narrative and Expository Text -- Concluding Thoughts -- APPENDIX A Checklist for Evaluating Informational Literature -- APPENDIX B Common Core State Standards (CCSS) Checklists -- Kindergarten CCSS Checklist -- First Grade CCSS Checklist -- Second Grade CCSS Checklist -- APPENDIX C Lesson Plan Template -- APPENDIX D Topical List of Informational Literature -- APPENDIX E Annotated Bibliography of Children's Books.
Includes bibliographical references : (p. 255-259) and index.
Text in English.
Keywords: Language arts (Elementary).; Exposition (Rhetoric) -- Study and teaching (Elementary).